Surgical management of complicated Stanford type A aortic dissection with subdural haematoma due to constrictive pericarditis—a case report - He, Weibo; Sun, Dongmei; Yao, Shiyuan; Wu, Yuan; Fan, Linglin (Frontiers in Cardiovascular Medicine, 2025)
Constrictive pericarditis, often resulting from pericardial adhesions secondary to chest radiotherapy or cardiac surgery, generally carries a favorable prognosis when surgical intervention is performed early. In contrast, extensive acute aortic dissection is associated with a significantly higher mortality rate, highlighting the critical importance of timely surgical intervention to improve patient outcomes. Here, we present a case involving a patient with a ruptured Stanford type A aortic dissection complicated by constrictive pericarditis, which led to the formation of a large pseudoaneurysm causing severe compression of the right atrium and markedly increasing the risk of mortality. The patient underwent successful emergency one-stage surgery and was discharged with a favorable recovery. This report uniquely highlights the management of two life-threatening conditions—type A aortic dissection and constrictive pericarditis—in a single surgical procedure, aiming to enhance patient survival and minimize complications. This case not only illustrates a successful life-saving intervention but also provides a strategic framework for cardiac surgeons, encouraging them to address complex, high-risk cases with an integrated approach.